2022
DOI: 10.1080/1060586x.2022.2049563
|View full text |Cite
|
Sign up to set email alerts
|

Who cares about sanctions? Observations from annual reports of European firms

Abstract: This paper uses textual analysis to examine how European corporations assess sanctions in their annual reports. Using observations from a panel of almost 11,500 corporate annual reports from 2014-2017, we document significant cross-country variation in how firms perceive Russia-related sanctions. Even after controlling for firm-level characteristics, cross-country differences remain for sentiments about sanctions and contexts in which sanctions are mentioned. We also examine the role of macroeconomic linkages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Existing studies have shown that economic sanctions have a greater negative impact on the sanctioned economy, linking sanctioning countries to more trade and investment (Davydov et al, 2022; Whang et al, 2013). Trade, finance and travel—the flow of goods, capital and people—are the main channels through which the world's economies are connected.…”
Section: Trends In Multilateral Economic Sanctions and Theoretical Ex...mentioning
confidence: 99%
“…Existing studies have shown that economic sanctions have a greater negative impact on the sanctioned economy, linking sanctioning countries to more trade and investment (Davydov et al, 2022; Whang et al, 2013). Trade, finance and travel—the flow of goods, capital and people—are the main channels through which the world's economies are connected.…”
Section: Trends In Multilateral Economic Sanctions and Theoretical Ex...mentioning
confidence: 99%
“…Ahn and Ludema (2020) also investigate the effects of sanctions against Russian firms, showing that the targeted approach to sanctions (i.e., smart sanctions), was new but efficient since they negatively affected the firms' activities while causing minimal 'collateral' damage. Davydov et al (2021) analyse how European firms perceive Russia-related sanctions. study the impact of sanctions against Russia (and other countries like Iran, Cuba, and Myanmar) on the probability of serving a market at the firm-level using monthly custom data on French firms.…”
Section: About the Authormentioning
confidence: 99%
“…The first group unites researchers who focus on political sanctions as a tool to constrain the development of the Russian economy. In general, experts agree that the collective political pressure of the West on Russia increases confrontational risks in international relations (Belín & Hanousek, 2021;Davydov et al, 2022), and can lead to unpredictable situations (Likhacheva, 2021;Timofeev, 2021), including cascading effects for the global economy (Fisher, 2017;Gould-Davies, 2020;Libmann, 2015). At the same time, as history shows, direct or indirect political restrictions against any significant actor of international economic relations can trigger the processes of diversification and modernization of the target's economy (Kaempfer & Lowenberg, 2007;Nitsevich et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…What is more, sanctions or Russia's reaction to them can trigger a process of economic transformations (regional shift, import substitution, etc.). Their impact on the global economy is quite difficult to assess given the increasing interdependence between multiple economic actors (Connolly, 2015;Davydov et al, 2022;Korhonen, 2019), as well as the increasing chaoticity in the system of international political relations and weak predictability of global development trends (Andermo, 2021;Belozerov & Sokolovskaya, 2022;Mardones, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%